T?cnica de lineariza??o por pr?-distor??o empregando um modelo n?o linear exponencial - Calil J?nior, Laert (2003)
The study of the undesirable non-linear effects caused by the inherent behavior of the active devices, becomes increasingly important due to the applications in our day-to-day. Whether it's electronic entertainment equipment or the telecommunication systems we're dependent on, such as radio links, microwaves, and cellular communications, they all depend on RF power amplifiers for their operation. The purpose of this work was to summarize information about the linearization techniques of RF power amplifiers, delving into the exponential mathematical model proposed by Clarke-Hess for amplifiers in large signals that use BJT devices and present a new linearization technique based on this model . Theoretical fundamental results involving the theory of nonlinear effects in amplifiers in large signals in the RF range are presented in the course of the work. Simulations using professional commercial programs: Genesys / Harbec of Eagleware and ADS - Advanced Design System of Agilent allowed to verify the convergence between the results obtained by the exponential model and the numerical simulation of the circuits. In addition, some simulations were performed with MatLab.